2018
DOI: 10.1017/s1751731118002276
|View full text |Cite
|
Sign up to set email alerts
|

Review: Selecting for improved feed efficiency and reduced methane emissions in dairy cattle

Abstract: It may be possible for dairy farms to improve profitability and reduce environmental impacts by selecting for higher feed efficiency and lower methane (CH4) emission traits. It remains to be clarified how CH4 emission and feed efficiency traits are related to each other, which will require direct and accurate measurements of both of these traits in large numbers of animals under the conditions in which they are expected to perform. The ranking of animals for feed efficiency and CH4 emission traits can differ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 79 publications
5
83
0
4
Order By: Relevance
“…Both the methane and the metabolizable energy of the diet depend on the digestion process in the rumen-an increased digestion can provide more nutrients for the animal metabolism, as well as increased enteric methane production when roughage diets are consumed. In the review of Richardson and Herd [41], digestibility was assumed to account for 10% of the variation in RFI on average in beef cattle, while Lovendahl et al [42], in their review of dairy cattle, concluded that between-cow variation in digestibility alone was too small to explain the observed variation in feed efficiency. Nonetheless, higher digestibility of DM or NDF was found in low-RFI as compared to high-RFI cattle in the studies of McDonnell et al [15] and Oliveira et al [17] with beef cattle and Olijhoek et al [43] with dairy Holstein cows.…”
Section: Calculated Growth and Methane Efficiency Traitsmentioning
confidence: 99%
“…Both the methane and the metabolizable energy of the diet depend on the digestion process in the rumen-an increased digestion can provide more nutrients for the animal metabolism, as well as increased enteric methane production when roughage diets are consumed. In the review of Richardson and Herd [41], digestibility was assumed to account for 10% of the variation in RFI on average in beef cattle, while Lovendahl et al [42], in their review of dairy cattle, concluded that between-cow variation in digestibility alone was too small to explain the observed variation in feed efficiency. Nonetheless, higher digestibility of DM or NDF was found in low-RFI as compared to high-RFI cattle in the studies of McDonnell et al [15] and Oliveira et al [17] with beef cattle and Olijhoek et al [43] with dairy Holstein cows.…”
Section: Calculated Growth and Methane Efficiency Traitsmentioning
confidence: 99%
“…A positive RFI value means feed intake is greater than expected and indicates an inefficient animal, whereas a negative value means intake is less than expected and indicates a more efficient animal. Research on methods to estimate RFI, the biological basis of its variation, and its utility in genomic selection of dairy cattle continues to evolve since Koch et al (1963) first introduced RFI as an estimate of metabolic efficiency of growing beef cattle (e.g., see reviews by Berry and Crowley, 2013;Connor, 2015;Løvendahl et al, 2018). Implementation of genomic selection for improved (reduced) RFI in dairy cattle has been proposed (Gonzalez-Recio et al, 2014;Pryce et al, 2014;VandeHaar et al, 2016), although present accuracy of genomic breeding values is generally low (≤0.4), in part due to limited availability of RFI phenotypes from genotyped individuals (Pryce et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pour des femelles laitières, si les approches basées sur la CMJR semblent également pertinentes, elles nécessitent de longues périodes de mesures d'ingestion pour prendre en compte la dynamique de la lactation, même si les travaux récents montrent que les mesures en milieu de lactation sont les plus représentatives de l'ensemble du cycle. Le modèle de calcul des CMJR pour les vaches laitières utilise le lait et la composition du lait, le poids et de façon moins systématique les variations de poids ou d'état corporel pour tenir compte des variations des réserves (Løvendahl et al, 2018). L'utilisation de ces indicateurs montre une variabilité importante de la CMJR dans la plupart des espèces.…”
Section: Comment Mesurer L'efficience Alimentaire Des Animaux Dans Ununclassified
“…En pratique, la sélection permettrait de gagner de l'ordre de 10 % sur la consommation d'aliments pour des animaux en croissance, mais probablement moins sur les femelles laitières. La faible corrélation entre l'efficience calculée en début de lactation et celle observée sur toute la lactation (Fischer, 2017 ;Løvendahl et al, 2018). D'autres approches analogues basées sur la production résiduelle au lieu de l'ingestion résiduelle ont été proposées à partir de modèles destinés à expliquer la production (lait ou gain de poids) à partir de variables décrivant l'ingestion et le poids de l'animal.…”
Section: Comment Mesurer L'efficience Alimentaire Des Animaux Dans Ununclassified